1993
DOI: 10.1128/jb.175.23.7720-7723.1993
|View full text |Cite
|
Sign up to set email alerts
|

Energy-dependent degradation of lambda O protein in Escherichia coli

Abstract: Protein 0 of bacteriophage A is a short-lived protein which has a key role in the replication of the phage DNA in Escherichia coli. Here we present evidence that XO degradation is energy dependent: it is impaired by cyanide and a-methylglucoside, both of which inhibit cellular energy metabolism. Removal of these inhibitors restored the degradation of XO. Our experiments suggest that limited Amounts of cellular energy are sufficient to support XO degradation. In addition, degradation of XO protein is prevented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 28 publications
2
14
0
Order By: Relevance
“…Later reports demonstrated that the O protein has a chemical half-life of just 1.5 min in -infected cells (48 -50) and that an ATP-dependent protease mediated this rapid turnover (50,51). In light of the identification of the responsible protease as the ClpP/ClpX protease (6, 7) and of recent findings that O protein bound to the replication origin is, both in vivo (52) and in vitro (53), stabilized against proteolytic attack, it is likely that the studies reported here will provide useful insights into the O turnover process in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Later reports demonstrated that the O protein has a chemical half-life of just 1.5 min in -infected cells (48 -50) and that an ATP-dependent protease mediated this rapid turnover (50,51). In light of the identification of the responsible protease as the ClpP/ClpX protease (6, 7) and of recent findings that O protein bound to the replication origin is, both in vivo (52) and in vitro (53), stabilized against proteolytic attack, it is likely that the studies reported here will provide useful insights into the O turnover process in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, several bacterial energydependent proteases have been shown to degrade regulatory proteins of bacteriophages. For example, E. coli ClpP degrades protein O of the phage, which has a main role in the replication of viral DNA (30). Similarly, it is possible that ClpP degrades some 29 proteins required for viral development.…”
Section: Resultsmentioning
confidence: 99%
“…The turnover rate of Phd is slow relative to a number of rates of energy-dependent proteolyses reported in the literature (8,24). This slow turnover (a half-life of almost two bacterial generations) minimizes the risk that variations in protease activity might lead to premature activation of Doc.…”
Section: Involvement Of Clpxp In P1mentioning
confidence: 95%
“…The few substrates identified so far for the recently discovered ClpXP protease of E. coli (9) are all encoded by bacteriophages: the 0 replication protein of bacteriophage A (298 amino acid residues) (10,24), mutant forms of the bacteriophage Mu repressor protein (196 amino acid residues) (32), and the antidote protein Phd (73 amino acid residues) of bacteriophage P1. Phd, being the smallest of the three, would appear to be a promising substrate for studies of protease target specificity.…”
Section: Involvement Of Clpxp In P1mentioning
confidence: 99%